CREATING RELIGIOUS CHARACTER AND DISCIPLINE THROUGH TAHFIDZ QUR'AN ACTIVITIES - Rizka Amelia (JURNAL SOCIUS, 2022)
This research aims 1)Describe and explain in depth the concept of religious character formation and discipline through tahfidz Al-Qur'an activities in Kindergarten Kindergarten Al Hamid and TK Blossom Banjarmasin, 2) Describe and explain in depth the process of religious character and discipline through tahfidz Al-Qur'an activities Qur'an in Kindergartens TK Al Hamid and TK Blossom Banjarmasin, 3) Describe and explain in depth the religious character of alumni as a result of the method of forming religious character and discipline through tahfidz Al-Qur'an activities in Kindergarten of Al Hamid Kindergarten and Blossom Kindergarten Banjarmasin. The method used is qualitative. The results of the study obtained from interview and observational data showed that the activity of tahfidz Al-Qur'an was the initial strategy applied by the teacher in instilling religious and disciplined characters in their students. The program for reciting the Koran, praying Duha, praying and praying Dzuhur together.